ANALISIS BENTUK INTERAKSI SOSIAL ASOSIATIF BEDA AGAMA PADA MAHASISWA PRODI PENDIDIKAN SOSIOLOGI FKIP UNTAN - Nuraddin, M.; Salim, Izhar; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe title of this research is "Analysis of the Forms of Social Interaction Associative of Religious Differences in Students of the FKIP Untan Sociology Education Study Program". The research method used is descriptive method with a form of qualitative research. The data source of this study were students of the Sociology Education Study Program FKIP Untan. Data collection techniques in this study are through observation, interviews and documentation, while the data collection tools used are observation guides, interview guides and documentation tools. The results showed that 1. Interaction between different religions in FKIP Untan Sociology Education Study Program students through spontaneous student collaboration, namely cooperation carried out without any orders from anyone, such as helping friends of different religions who experience disasters. Besides that there is a group discussion which is ordered by the lecturer during the course. 2. Through the 5th semester student accommodation FKIP Sociology Education Study Program Untan respects each other's differences of opinion and mutual tolerance. In resolving differences of opinion held a compromise or discussion.Â Keywords: Difference in Religion, Interaction, Students.